Analisis Bibliometrik Implementasi Media Augmented Reality (AR) dalam Pembelajaran Ekonomi di Pendidikan Tinggi - Kusworo, Kusworo; Yuni Rahayu, Purwati; Putranto, Ivan (Pamulang university, 2025)
The process of learning economics in higher education units by using learning media oriented to Augmented Reality (AR) provides a real learning experience for students and is relevant to increasing understanding of both theory and practice. The purpose of this research is to analyze literature studies related to Augmented Reality (AR) in economic learning in higher education units. This research uses bibliometric analysis method in analyzing various published literatures. Data collection was carried out by documenting and reviewing related articles published in the range of 2014 to 2024. Based on the search results, a total of 800 relevant articles were found based on the keyword criteria used as the main study. In the next stage, the articles were coded and analyzed based on the relevance to learning on campus. Based on the results of the analysis of existing literature, it can be seen that the implementation of Augmented Reality (AR) in economic learning is quite widely studied by researchers, it's just that AR studies on campus still have opportunities to be studied because they can increase motivation and provide experience to students in meaningful learning. Keywords: Augmented Reality; Economic Learning; Learning Media